2022
DOI: 10.1155/2022/1984742
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Intervertebral Disc Degeneration: Pathophysiology, Signaling Pathway, and Therapy

Abstract: Intervertebral disc degeneration (IDD), characterized as decreased proteoglycan content, ossification of endplate, and decreased intervertebral height, is one of the major reasons of low back pain, which seriously affects the quality of life and also brings heavy economic burden. However, the mechanisms leading to IDD and its therapeutic targets have not been fully elucidated. Oxidative stress refers to the imbalance between oxidation and antioxidant systems, between too many products of reactive oxygen specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 119 publications
1
11
0
Order By: Relevance
“…It is suggested that these hub FRDEGs are closely related to oxidative stress. Oxidative stress has played key roles in the pathogenesis and development of IDD, as reported in previous studies from ours and others (34)(35)(36)(37) was an independent risk factor for IDD and it accelerated IDD development via oxidative stress and ferroptosis in endplate chondrocytes (22). Besides, oxidative stress could induce ferroptosis in AF cells and NP cells in an autophagy-dependent way during IDD process (39).…”
Section: Discussionsupporting
confidence: 52%
“…It is suggested that these hub FRDEGs are closely related to oxidative stress. Oxidative stress has played key roles in the pathogenesis and development of IDD, as reported in previous studies from ours and others (34)(35)(36)(37) was an independent risk factor for IDD and it accelerated IDD development via oxidative stress and ferroptosis in endplate chondrocytes (22). Besides, oxidative stress could induce ferroptosis in AF cells and NP cells in an autophagy-dependent way during IDD process (39).…”
Section: Discussionsupporting
confidence: 52%
“…It has been reported that overwhelming oxidative stress exacerbates inflammation during IVDD by damaging bioactive molecules and regulating related signaling pathways. 14 When the redox homeostasis between production and removal of ROS/RNS is impaired, the overproduced and accumulated pro-oxidants are regarded as the culprit of oxidative stress. 11 ROS and RNS can be scavenged by hydrogels supplemented with antioxidative properties.…”
Section: Resultsmentioning
confidence: 99%
“…nucleic acids and proteins) and regulating signaling pathways, leading to the apoptosis and senescence of cells, and the overexpression of inflammatory cytokines. [12][13][14][15] Then, oxidative stress and inflammation promote each other, which accelerates the degeneration of NP. 16,17 Naturally, futile inhibition of the above-mentioned overactive inflammatory process by self-regulation is more likely to deteriorate IVDD.…”
Section: Introductionmentioning
confidence: 99%
“…[62][63][64][65] Over time, the fibrotic repair process embargoes with angiogenesis distributing into the disc. [66] Apart from the increased inflammatory cytokines following penetration, [67,68] excessive blood and oxygen accumulate in the discs, causing a ROS burst, [69] which in turn stimulates further peroxidation of lipids, [24] proteins, and even nucleic acids, [70] leading to detrimental signaling pathway activation. [71] During this process, the hemoglobin from the newly-formed blood vessel increases in the disc, inducing an overload of Fe ions and ferroptosis of NP cells after being metabolized and degraded.…”
Section: Discussionmentioning
confidence: 99%